CYP3A pharmacogenetic association with tacrolimus pharmacokinetics differs based on route of drug administration. (April 2018) - Pasternak, Amy L; Zhang, Lu; Hertz, Daniel L
Tacrolimus is prescribed to the majority of transplant recipients to prevent graft rejection, and although patients are maintained on oral administration, nonoral routes of administration are frequently used in the initial post-transplant period. CYP3A5 genotype is an established predictor of oral tacrolimus dose requirements, and clinical guideline recommendations exist for CYP3A5 -guided dose selection. However, the association between CYP3A5 and nonoral tacrolimus administration is currently poorly understood, and differs from the oral tacrolimus relationship. In addition to CYP3A5, other pharmacogenes associated with CYP3A activity, including CYP3A4, CYP3A7 and POR have also been identified as predictors of tacrolimus exposure. This review will describe the current understanding of the relationship between these pharmacogenes and tacrolimus pharmacokinetics after oral and nonoral administration.